Division Play and Outcome Uncertainty in Sports Leagues. (June 2023) - Lee, Young Hoon; Fort, Rodney
The analysis of outcome uncertainty (OU) and competitive balance (CB) has been of overwhelming importance in sports economics. Surprisingly, there is little work on the impact of the structure of play on either OU or CB. Balanced and unbalanced schedules, and division play have been used to analyze biasedness of CB measures. And the impact of the introduction of unbalanced schedules on OU has been analyzed. But the impact of the introduction of both unbalanced schedules and division play on OU has not been analyzed. In this paper, we assess the impacts on OU, for given choices of CB (OU/CB) of moving to division play. This includes the impact of schedule imbalance, division strength, the number of teams, and the number of divisions. We also obtain estimates of their marginal impacts on OU/CB via numerical analysis and regression. The results are compared to OU/CB from unbiased estimators, for the case of the introduction of division play in Major League Baseball. The results suggest that the approach is useful and there are policy implications.